The highly selective mGlu2 receptor positive allosteric modulator LY‐487, 379 alleviates l‐DOPA‐induced dyskinesia in the 6‐OHDA‐lesioned rat model of Parkinson's disease. (12th February 2020) - Hamadjida, Adjia; Sid‐Otmane, Lamia; Kwan, Cynthia; Frouni, Imane; Nafade, Vaidehi; Bédard, Dominique; Gagnon, Dave; Wallman, Marie‐Josée; Rouillard, Claude; Parent, André; Parent, Martin; Huot, Philippe
Abstract: l ‐3, 4‐Dihydroxyphenylalanine (l ‐DOPA) is the most effective treatment for Parkinson's disease (PD), but its use over a long period is marred by motors complications such as dyskinesia. We previously demonstrated that selective metabotropic glutamate 2/3 (mGlu2/3 ) receptor activation with LY‐354, 740 alleviates dyskinesia in the 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)‐lesioned marmoset and the 6‐hydroxydopamine (6‐OHDA)‐lesioned rat. Here, we sought to determine the role played by selective mGlu2 activation in the anti‐dyskinetic effect of mGlu2/3 stimulation and have investigated the effect of the highly selective mGlu2 positive allosteric modulator LY‐487, 379 at alleviating established, and preventing the development of, l ‐DOPA‐induced dyskinesia in the 6‐OHDA‐lesioned rat. First, dyskinetic 6‐OHDA‐lesioned rats were administered l ‐DOPA in combination with LY‐487, 379 (0.1, 1 and 10 mg/kg) or vehicle, and the severity of dyskinesia was determined. Second, 6‐OHDA‐lesioned rats were administered LY‐487, 379 (0.1 or 1 mg/kg), started concurrently with l ‐DOPA, once daily for 22 days, and dyskinesia severity was evaluated weekly for four consecutive weeks. We also assessed the effect of LY‐487, 379 on l ‐DOPA anti‐parkinsonian effect. We found that acute challenges of LY‐487, 379 0.1 mg/kg in combination with l ‐DOPA, significantly diminished dyskinesia severity, by ≈54% ( p < .01), when compared to vehicle. Moreover, animals treated with l ‐DOPA/LY‐487, 379 0.1 and 1 mg/kg during the dyskinesia induction phase exhibited milder dyskinesia, by ≈74% and ≈61%, respectively (both p < .01), when compared to l ‐DOPA/vehicle. LY‐487, 379 did not impair l ‐DOPA anti‐parkinsonian activity. These results suggest that mGlu2 activation may be an effective and promising therapeutic strategy to alleviate the severity and prevent the development of dyskinesia. Abstract : Highly selective mGlu2 activation alleviates l ‐DOPA‐induced AIMs in the hemi‐parkinsonian rat.